Low-carbon fluidized solidification of construction spoil: Stepwise synergistic mechanism and C-(A)-S-H gel formation via quaternary industrial waste blending design - Zhong Li; Jihui Zhao; Xuan Qiu; Yinuo Zhao; Haidong Li; Ningning Wang; Changyi Tang; Xin Zhao; Li Zhang; Jun Quan (Applied Clay Science, 2026)

Shear-driven dynamic fracture in rock joints with a single locked convex asperity structure under constant normal stiffness - Yuheng Fang; Shili Qiu; Shishu Zhang; Zhongmin Tang; Rujun Mo; Lexin Jia; Quan Jiang; Shaojun Li; Kaidi Deng; Zhenkun Xie (International Journal of Rock Mechanics and Mining Sciences, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

Applications of multiomics technologies to thermotolerant yeasts in industrial fermentation - Xuexue Rao; Meiyan Li; Linling Li; Quan Yuan; Xiaodan Wang; Wentao Cao; Shuyi Qiu; Xiaoye Luo (International Journal of Food Microbiology, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

A new sesquiterpene lactone and other phytochemicals from the fruits of Magnolia grandiflora and their chemophenetic significance - Qiu-Ye Zhao; Zhen-Quan Li; Shi-Huan Yin; Hui-Ling Zhou; Xin-Ying Wang; Wei-Yang Feng; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Nonstationary agricultural drought risk under compound meteorological drought and hot conditions - Quan Zhang; Ziyang Lu; Jiaolong Ying; Yue Qiu; Panpan Wang; Zhipeng Xu; Dongxiao Xu; Yongping Li (Journal of Hydrology, 2026)

Regulated zirconium-based metal organic frameworks via ligand-defect and rare earth post-coordination: A synchronized strategy for enhancing Cr (VI) adsorption and phenol photodegradation - Yongxing Sun; Zuguang Li; Jing He; Kaijun Quan; Hongdeng Qiu; Jia Chen (Chemical Engineering Journal, 2026)

Multiscale Fracture Evolution in Deep Hard Rock Masses Under Strong Excavation Disturbances: Stress-Mineral Synergy Unraveled Through Integrated 3D DEM–FDM Modeling and Borehole Monitoring - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Shi-Li Qiu; Yong Xia (Rock Mechanics and Rock Engineering, 2026)

Stochastic Characterization of In Situ Stress Field in Deep Rock Masses Based on Stochastic Stratigraphic Reconstruction Technique - Zhenkun Xie; Shili Qiu; Shaojun Li; Quan Jiang; Dingping Xu; Minzong Zheng (Rock Mechanics and Rock Engineering, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metal nanoparticles transport in the subsurface: a review - Quan Wan; Miaoyue Zhang; Man Zhao; Erwin Klumpp; Roland Bol; Kengbo Ding; Zhuobiao Ni; Jingjing Li; Chao Jin; Rongliang Qiu (Environmental Chemistry Letters, 2026)

Associations of prenatal per- and polyfluoroalkyl substances exposure with glucose homeostasis and gestational diabetes mellitus: A systematic review and meta-analysis - Feng Quan; Chuanzi Gao; Jason T. Magnuson; Yu Li; Wenhui Qiu; Rongrong Xuan; Haiyan Lu; Yi Zheng (Journal of Hazardous Materials, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Amino-directed shifting ethylene/acetylene/ethane separation in pore-space-partitioned metal-organic frameworks - Li-Qiu Yang; Yan-Fei Li; Jia-Yao Liu; Ying Wang; Wen-Yu Yuan; Quan-Guo Zhai (Chemical Engineering Journal, 2025)

Failure Mechanisms of Granite in Deep Underground Caverns Influenced by Rock Veins: Insights from DEM-FDM Cross-Scale Coupling and Moment Tensor Analysis - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Kang Bian; Shi-Li Qiu (Computers and Geotechnics, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

The impact of counter-flow fin-shape rods cylinder and its geometric parameters on wind-induced vibration energy harvester - Jian Qiu; Qiaoya Lv; Hanpei Xu; Dongling Li; Quan Wen (Ocean Engineering, 2025)

Biostimulants accelerate lignin degradation in semi-aerobic landfills, assisting overall lifecycle management and sustainable development of landfills - Mingxing Li; Hui Jiang; Ruiding Li; Lifeng Liu; Wendong Liu; Yong Xie; Wenchan Wu; Xing Li; Yulan Chen; Quan Deng; Zhongping Qiu (Journal of Cleaner Production, 2025)

Excavation damage mechanism of deep buried layered fractured rock mass based on three-dimensional bonded block damage model - Zhenkun Xie; Shili Qiu; Shaojun Li; Quan Jiang; Dingping Xu; Minzong Zheng (Computers and Geotechnics, 2025)

Robust localization and tracking control of high-clearance robot system servicing high-throughput wheat phenotyping - Qinghan Hu; Zhengqiang Fan; Xihai Zhang; Na Sun; Xuefeng Li; Quan Qiu (Computers and Electronics in Agriculture, 2025)

Effects of Dietary Chlorogenic Acid on the Growth, Lipid Metabolism, Antioxidant Capacity, and Non-Specific Immunity of Asian Swamp Eel (Monopterus albus) - Hang Yang; Chengcheng Wu; Quan Yuan; Weiwei Lv; Junqiang Qiu; Mingyou Li; Qinghua Zhang; Wenzong Zhou (Fishes, 2024)
To investigate the dietary effects of chlorogenic acid (CGA) on the growth performance, lipid metabolism, antioxidant activity, and non-specific immunity of Asian swamp eel (Monopterus albus) during the domestication stage, a 28-day feeding experiment was conducted to supplement with CGA at levels of 0 (Cont.), 250 (CGA 0.50%), 500 (CGA 1.00%), and 750 (CGA 1.50%) mg/kg·bw by feeding with yellow mealworm (Tenebrio molitor). Compared with the control group, the addition of 250–750 mg/kg of CGA significantly increased the weight-gain rate (WG) of M. albus, and the CGA 1.0% group displayed the highest value. The content of hemoglobin and high-density lipoprotein in all CGA groups was markedly elevated (p

The constrained permutation flowshop problem: An effective two-stage iterated greedy algorithm to minimize weighted tardiness - Qiu-Ying Li; Quan-Ke Pan; Liang Gao; Hong-Yan Sang; Xian-Xia Zhang; Wei-Min Li (Swarm and Evolutionary Computation, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Regulation and synthesis of metal–organic frameworks through mixed-ligand strategy: A pathway to enhance adsorption of perfluoroalkyl acids - Yongxing Sun; Kaijun Quan; Jing He; Jia Chen; Zuguang Li; Hongdeng Qiu (Chemical Engineering Journal, 2024)

Estimating the Mechanical Properties of Rocks and Rock Masses Based on Mineral Micromechanics Testing - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shu-qian Duan; Huai-sheng Xu; Quan Jiang; Shi-li Qiu (Rock Mechanics and Rock Engineering, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Tunnel lining crack detection model based on improved YOLOv5 - Shuqian Duan; Minghuan Zhang; Shili Qiu; Jiecheng Xiong; Hao Zhang; Chenyang Li; Quan Jiang; Yongyuan Kou (Tunnelling and Underground Space Technology, 2024)

Modeling damage evolution in granite under temperature using a thermo-mechanical grain-based FDEM model - Shirui Zhang; Shili Qiu; Quan Jiang; Chengzeng Yan; Liangyin Zhou; Xinhong Li (Computers and Geotechnics, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Viologen-based ionic conjugated mesoporous polymer as the electron conveyer for efficient polysulfide trapping and conversion - Hai-Yang Li; Zhong-Shan Li; Gang-Hao Qiu; Rou-Rou Zhang; Ya-Rui Wang; Feng Wang; Ren-Wu Huang; Xiao-Fei Liu; Shuang-Quan Zang (Science Bulletin, 2024)

Heavy metal migration dynamics and solid-liquid distribution strategy in abandoned tailing soils - Bohan Wu; Quan Wan; Xiao Li; Shukun Lin; Yanqi Jiang; Xu Yang; Jingjing Li; Qingqi Lin; Jean Louis Morel; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Exploring microbial degradation of polyamide 4 in soils: Unveiling degradation mechanisms, pathways, and the contribution of strain NR4 - Li Wang; Ziwei Zhang; Di Zhang; Yongjun Qiu; Yibing Wang; Shu Quan; Liming Zhao (Journal of Cleaner Production, 2023)

A simulated drier climate reduces growth and alters functional traits of Eucalyptus trees: A three-year experiment in South China - Ling Yang; Jiejun Kong; Yaqian Gao; Zetao Chen; Yubiao Lin; Shucai Zeng; Yan Su; Jiyue Li; Qian He; Quan Qiu (Forest Ecology and Management, 2023)

The alkaloids with neuroprotective effect from the root bark of Ailanthus altissima - Qing Shao; Tian-Yi Li; Wei Quan; Hui Wang; Ke-Yu Yan; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu (Natural Product Research, 2023)

Dry-season irrigation further promotes the growth of Eucalyptus urophylla × E. grandis plantations under the conventional fertilization - Lei Hua; Fei Yu; Quan Qiu; Qian He; Yan Su; Xiaodong Liu; Jiyue Li (New Forests, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

A novel peridynamic solution for modelling saturated soil-pore fluid interaction in liquefaction analysis - Quan Gu; Zhe Lin; Lei Wang; Zhijian Qiu; Surong Huang; Shaofan Li (Computers and Geotechnics, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Efficacy of Aidi injection combined with chemotherapy, radiotherapy or chemoradiotherapy for unresectable esophageal cancer treatment: A meta-analysis and systematic review of 29 randomized controlled trials based on Asian populations (China) - Jinsheng Huang; Teng Fan; Yuming Rong; Xujia Li; Qi Jiang; Jun Kan; Huijuan Qiu; Qi Quan; Bei Zhang; Guifang Guo (European Journal of Clinical Pharmacology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

An Insight into the Mechanical and Fracture Characterization of Minerals and Mineral Interfaces in Granite Using Nanoindentation and Micro X-Ray Computed Tomography - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shi-li Qiu; Quan Jiang (Rock Mechanics and Rock Engineering, 2023)

New approach to monitoring and characterizing the directionality of electromagnetic radiation generated from rock fractures - Menghan Wei; Dazhao Song; Xueqiu He; Quan Lou; Zhenlei Li; Liming Qiu; Shengquan He (Journal of Applied Geophysics, 2023)

Soil and water conservation measures reduce erosion but result in carbon and nitrogen accumulation of red soil in Southern China - Yan Zhang; Xin Qin; Quan Qiu; Ronggang Yu; Yufei Yao; Haiqiang Li; Mingan Shao; Xiaorong Wei (Agriculture, Ecosystems & Environment, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Joint effects of air PM2.5 and socioeconomic dimensions on posted emotions of urban green space visitors in cities experiencing population urbanization: A pilot study on 50 cities of East China - Qian He; Yue Wang; Quan Qiu; Yan Su; Yang Wang; Hongxu Wei; Jiyue Li (Science of The Total Environment, 2023)

Whole transcriptome sequencing and competitive endogenous RNA regulation network construction analysis in benzo[a]pyrene-treated breast cancer cells - Qiu-feng Lao; Qing-quan Zhang; Zi-peng Qiao; Sheng-le Li; Liu Liu; Francis L. Martin; Wei-yi Pang (Science of The Total Environment, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Altered effective connectivity within the cingulo-frontal-parietal cognitive attention networks in chronic low back pain: a dynamic causal modeling study - Cui Ping Mao; Hua Juan Yang; Qiu Juan Zhang; Quan Xin Yang; Xiao Hui Li (Brain Imaging and Behavior, 2022)

CaMKIIα Signaling Is Required for the Neuroprotective Effects of Dl-3-n-Butylphthalide in Alzheimer’s Disease - Bing-qiu Li; Ling-zhi Xu; Fang-yu Li; Ying Li; Yu Zhao; Heng Zhang; Mei-na Quan; Jian-ping Jia (Molecular Neurobiology, 2022)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

The isolation of two new compounds from Valeriana jatamansi - Li-Qiu Quan; Qian Zhao; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2020)

Effect of Rock Properties on Electromagnetic Radiation Characteristics Generated by Rock Fracture During Uniaxial Compression - Menghan Wei; Dazhao Song; Xueqiu He; Zhenlei Li; Liming Qiu; Quan Lou (Rock Mechanics and Rock Engineering, 2020)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

Characteristic Stress Levels and Brittle Fracturing of Hard Rocks Subjected to True Triaxial Compression with Low Minimum Principal Stress - Yao-Hui Gao; Xia-Ting Feng; Xi-Wei Zhang; Guang-Liang Feng; Quan Jiang; Shi-Li Qiu (Rock Mechanics and Rock Engineering, 2018)

Onosmanones A and B, two novel quinonoid xanthenes from Onosma paniculatum - Li-Qiu Quan; Wei-Feng Dai; Fei Li; Yan-Hong Li; Xuan-Qin Chen; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2018)

A morphophysiological analysis of the effects of drought and shade on Catalpa bungei plantlets - Junwen Wu; Jiyue Li; Yan Su; Qian He; Junhui Wang; Quan Qiu; Jianwei Ma (Acta Physiologiae Plantarum, 2017)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Virus-binding activity of the truncated C subunit of porcine aminopeptidase N expressed in Escherichia coli - Dongbo Sun; Hongyan Shi; Jianfei Chen; Donghua Guo; Quan Liu; Xianjing He; Jun Bao; Yunfeng Wang; Huaji Qiu; Li Feng (Biotechnology Letters, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Exercise benefits cardiovascular health in hyperlipidemia rats correlating with changes of the cardiac vagus nerve - You-Hua Wang; Hao Hu; Sheng-Peng Wang; Zhen-Jun Tian; Quan-Jiang Zhang; Qiu-Xia Li; You-You Li; Xiao-Jiang Yu; Lei Sun; Dong-Ling Li; Bing Jia; Bing-Hang Liu; et al. (European Journal of Applied Physiology, 2010)

Effect of floral morphology on fruit set in Epimedium sagittatum (Berberidaceae) - Yun-xiang Li; Qiu-mei Quan; Gen-lou Sun (Plant Systematics and Evolution, 2009)

A Novel Camptothecin Derivative Incorporated in Nano-Carrier Induced Distinguished Improvement in Solubility, Stability and Anti-tumor Activity Both In Vitro and In Vivo - Min Han; Cai-Xia He; Qiu-Li Fang; Xiao-Chun Yang; Yuan-Yuan Diao; Dong-Hang Xu; Qiao-Jun He; Yong-Zhou Hu; Wen-Quan Liang; Bo Yang; Jian-Qing Gao (Pharmaceutical Research, 2009)

Isolation and characterization of three Sphingobium sp. strains capable of degrading isoproturon and cloning of the catechol 1,2-dioxygenase gene from these strains - Ji-Quan Sun; Xing Huang; Qiao-Ling Chen; Bin Liang; Ji-Guo Qiu; Shinawar Waseem Ali; Shun-Peng Li (World Journal of Microbiology and Biotechnology, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Long-term aerobic exercise protects the heart against ischemia/reperfusion injury via PI3 kinase-dependent and Akt-mediated mechanism - Kun-Ru Zhang; Hai-Tao Liu; Hai-Feng Zhang; Quan-Jiang Zhang; Qiu-Xia Li; Qiu-Jun Yu; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2007)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)